Implementing a novel approach to long‐term monitoring of butterfly communities in the Neotropics. Issue 4 (2nd February 2022) - Checa, Maria F.; Nogales, Sofia; Salazar, Patricio A.; Bustos, Leslie; Ojeda, Vernardo; Bustos, Alcy; Willmott, Keith R.
Abstract: Insects are facing severe threats of extinction. Long‐term data needed to develop effective conservation strategies are not yet available for precisely those areas where biodiversity peaks and negative impacts on species are particularly strong, such as Neotropical forests. One strategy to develop long‐term monitoring programmes worldwide has focused on training local people as 'parabiologists'. Although this model has been very successful, it requires significant, constant funding to cover wages. Here, we implemented a novel approach to address this logistical challenge and simultaneously achieve other beneficial outcomes. Based in Yasuní National Park, one of the world's most diverse protected areas, we started a monitoring scheme where park rangers hired by Ecuador's Ministry of the Environment implemented monitoring, after completing a capacity‐building programme. We describe this scheme and evaluate its performance in terms of the biological data gathered. Park rangers were able to identify sampled butterflies to species with a high degree of accuracy (85%), a key attribute for participatory monitoring programmes to be successful. The data gathered by park rangers resulted in commonly studied patterns of spatial and temporal variation that did not differ significantly from a comparable researcher dataset in this butterfly community. Our approach increases the likelihood of sustaining monitoring in the long‐term by reducing expenses such as lodging and wages. Furthermore, it also empowers local people, offers opportunities for public institutions to accomplish their environmental goals, and provides the potential for expansion to other highly threatened and important areas for biodiversity conservation. Abstract : After a short training programme with butterfly researchers, park rangers in Ecuador's Yasuní National Park have independently conducted a bi‐monthly butterfly monitoring programme since 2017. Park rangers correctly identified to species 85% of butterfly individuals collected. Data gathered by park rangers showed similar spatial and temporal patterns to data gathered by researchers, supporting the viability of this approach to studying long‐term trends in tropical butterfly communities.